UPAYA SATUAN TUGAS SAPU BERSIH MENANGANI PUNGUTAN LIAR ANGKUTAN JALAN DI KOTA DUMAI TAHUN 2021-2023 - Prastyo, Heru; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This thesis was motivated by the fact that many ministries/regional governments have not yet established a task force to eradicate extortion, the lack of public support for the task force in carrying out its duties to eradicate extortion in public services, and the lack of public reports. The task force will operate if it receives reports from the public. The purpose of this thesis is to determine the efforts of the Dumai City government's anti-extortion task force in 2021-2023 and to identify the inhibiting factors in the task force's efforts. The researcher used a descriptive qualitative approach. The location of this study was the Dumai City Transportation Agency. The types and sources of data in this study were primary data in the form of interviews and documentation conducted by the researcher, while secondary data consisted of reports, as well as profile documents, organizational structures, and tasks related to the Dumai City government's anti-extortion task force in 2021-2023. Interviews and documentation were used as data collection techniques. Meanwhile, data analysis was conducted using qualitative analysis. Based on the research results and discussion, it can be concluded that the Dumai City Government's Saber Pungli Task Force efforts from 2021 to 2023 have not been successful. This is due to several inhibiting factors, such as lack of public awareness, lack of transparency, lack of synergy, local government support, an ineffective reporting system, and weak law enforcement. Keywords: Efforts, Task Force to Clean Up Extortion and Illegal Levies